Merkhini interview and stories - Liudmila Merkhini; Valentina Dedyk (Alexander King, 2013)
Ludmila Merkhini introduces herself and tells some stories, plays her drum and sings several songs. Tells a few more stories. Supplementary recording by Sorokin of first part of first session with Merkhini. Covers some gaps in first part of recording. Other Koryak names: EtEnga (schwas), Iwlewut; Oryajanja - Even name Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra.